Winter sisters - Oliveira, Robin (New York Penguin, 2018)
New York, 1879: After an epic snow storm ravages the city of Albany, Dr. Mary Sutter, a former civil war surgeon, begins a search for two little girls, the daughters of close friends killed by the storm who have vanished without a trace. When what happened to them is revealed, the uproar that ensues tears apart families, reputations, and even the social fabric of the city, exposing dark secrets about some of the most powerful of its citizens, and putting fragile loves and lives at great risk.
Sequel to: My name is Mary Sutter.
Keywords: Women physicians -- Fiction; Missing children -- Fiction; Blizzards -- Fiction; FICTION -- Family Life; FICTION -- Historical; FICTION -- Literary; Blizzards; Missing children; Women physicia; New York (State) -- Albany; Fiction; Historical fiction; Historical fiction; Historical fiction